Comparison of cusp-overlap projection and standard three-cusp coplanar view during self-expanding transcatheter aortic valve replacement: A systematic review and meta-analysis - Chen, Yujing; Zhu, Gangjie; Liu, Xin; Wu, Weilin; Chai, Hui; Tao, Minjie; Kong, Dongmei; Li, Yingzi; Wang, Li (Frontiers in Cardiovascular Medicine, 2022)
Objective: Permanent pacemaker implantation (PPI) is a common complication after transcatheter aortic valve replacement (TAVR). Recently, the cusp-overlap projection (COP) technique was thought to be a feasible method to reduce PPI risk. However, the evidence is still relatively scarce. Therefore, this meta-analysis was performed to compare COP and standard three-cusp coplaner (TCC) projection technique. Methods: PubMed and EMBASE databases were systematically searched for relevant literature published from the inception (EMBASE from 1974 and PubMed from 1966) to April 16, 2022, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The primary outcome of interest was post-operative (including in-hospital and 30-day) permanent pacemaker implantation. Results: Total of 3647 subjects from 11 studies were included in this meta-analysis. Of those, 1453 underwent self-expanding TAVR using COP and 2194 using TCC technique. In a pooled analysis, the cumulative PPI incidence was 9.3% [95%confidence interval (CI): 6.9%-11.7%] and 18.9% (95%CI: 15.5%-22.3%) in the COP group and TCC group, respectively. The application of the COP technique was associated with a significant PPI risk reduction (I2=40.3% and heterogeneity chi-square p=0.070, random-effects OR: 0.49, 95%CI: 0.36-0.66, p <0.001). A higher implantation depth was achieved in the COP group compared with the TCC group [standardized mean difference (SMD) = -0.324, 95CI: (-0.469, -0.180)]. There was no significant difference between the two groups in second valve implantation, prosthesis pop-out, fluoroscopic time, post-operative left bundle branch block, mortality, stroke, moderate/severe paravalvular leakage, mean gradient and length of hospital stay. However, radiation doses were higher in the COP group [SMD =0.394, 95%CI: (0.216, 0.572), p<0.001] Conclusion: In self-expanding TAVR, the application of the cusp overlap projection technique was associated with a lower risk of permanent pacemaker implantation compared with the standard three-cusp coplaner technique.